Pineapple production and visions of regeneration– contrasting Costa Rican (agri)cultural paradigms - Schwarz, Luana (2025)
In a time when agricultural developments have led to the transgression of multiple planetary boundaries like climate change and biodiversity loss, deeply-rooted transformations in the agricultural sector are urgently needed. Vice versa, those very developments have put many farmers’ livelihoods in danger around the world. In the Costa Rican context, the “Desarrollo Sostenible a la Tica” points to the country’s well-known “green” sectors, but this paradigm has also caused a stark breach between the green image conveyed (“exceptionalismo verde”, en. “green exceptionalism”) and the actual social-ecological livelihoods of many rural communities and the state of the landscapes. However, this is not the only paradigm of sustainable development prevalent in the country. Regenerative Development, a term most prominently used in the context of Regenerative Agriculture, offers an alternative vision for Costa Rica’s futures encompassing agricultural production and culture in general. Following the stories shared by a diverse group of Costa Ricans interviewed on sustainable food systems and Regenerative Development, we drew a multifaceted picture of regeneration that includes both agricultural practices, as well as socio-cultural and relational dimensions. Referring to the power of paradigms as important scaffolds for people’s beliefs and decision-making in times of deep uncertainty, we thereafter compared the paradigm “Desarrollo Regenerativo” to the paradigm of “Desarrollo Sostenible a la Tica”. Putting these two paradigms in a dialogue, we delineated similarities and differences between them, to ultimately discuss possible ways forward: is there room for a (re-)conciliation and bridging of perspectives, or are the discrepancies between them too large, pointing to an unbridgeable gap and the need to fundamentally rethink the story of sustainable development the “Desarrollo Sostenible a la Tica” is currently telling? And what are potential implications for sustainable pineapple production?